2004
DOI: 10.1007/s11746-004-0901-z
|View full text |Cite
|
Sign up to set email alerts
|

Processing vegetable oils using nonporous denser polymeric composite membranes

Abstract: Membrane processing offers several advantages over conventional processes for edible oil refining. In recent years, processing solvent-extracted, screw-pressed, and used frying oils using nonporous denser polymeric composite membranes without pretreatment and addition of chemicals has been extensively investigated. In the present review, results obtained with real and model systems have been summarized and a comprehensive explanation is provided on the mechanism of rejection and differential permeation of oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 24 publications
2
39
0
2
Order By: Relevance
“…The transport in denser membranes is completely controlled by the solution diffusion mechanism in applications such as gas separation, pervaporation and vapor permeation [8] and also in the case of solute-solvent systems and liquid mixtures. The permeability in a nonporous membrane P m is equal to…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The transport in denser membranes is completely controlled by the solution diffusion mechanism in applications such as gas separation, pervaporation and vapor permeation [8] and also in the case of solute-solvent systems and liquid mixtures. The permeability in a nonporous membrane P m is equal to…”
Section: Theorymentioning
confidence: 99%
“…While in the case of nonporous membranes, the separation is due to the solution-diffusion effect. Extensive studies carried out by our research group on processing vegetable oils using nonporous membranes have been reviewed recently [7,8]. These studies showed that hydrophobic nonporous membranes possess very high selectivity to separate PL from undiluted as well as hexane diluted oils.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, both capital and energy costs are high. One alternative is the FFA distillation method which improves the product quality, the elimination of soap stock, and effluent reduction; its disadvantage is that strict oil pretreatment is required (Subramanian et al 2004). Another potential solution is the use of hybrid processes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…A more stable product and thus with better quality can be obtained by using membranes (Subramanian et al, 2004;Ribeiro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%